2022
DOI: 10.5194/acp-22-2795-2022
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Ocean SST-gradient-driven variations in aerosol and cloud evolution along Lagrangian cold-air outbreak trajectories

Abstract: Abstract. Atmospheric marine particle concentrations impact cloud properties, which strongly impact the amount of solar radiation reflected back into space or absorbed by the ocean surface. While satellites can provide a snapshot of current conditions at the overpass time, models are necessary to simulate temporal variations in both particle and cloud properties. However, poor model accuracy limits the reliability with which these tools can be used to predict future climate. Here, we leverage the comprehensive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…Previous work has found that some air masses can travel over the sea ice for extended periods before reaching the ocean (Silber and Shupe, 2022); however, a full investigation is beyond the scope of this study. Previous work has found a similarly steep decline in N d concentration following an MCAO (Abel et al, 2017;Sanchez et al, 2022). Two main drivers of this N d gradient in MCAOs have been proposed: the dilution of aerosol concentration through entrainment of air from the free troposphere and precipitation scavenging of aerosol from the below-cloud layer, which are considered further below.…”
Section: Droplet Number Concentrationmentioning
confidence: 87%
“…Previous work has found that some air masses can travel over the sea ice for extended periods before reaching the ocean (Silber and Shupe, 2022); however, a full investigation is beyond the scope of this study. Previous work has found a similarly steep decline in N d concentration following an MCAO (Abel et al, 2017;Sanchez et al, 2022). Two main drivers of this N d gradient in MCAOs have been proposed: the dilution of aerosol concentration through entrainment of air from the free troposphere and precipitation scavenging of aerosol from the below-cloud layer, which are considered further below.…”
Section: Droplet Number Concentrationmentioning
confidence: 87%
“…Globally, MCAOs are most frequent in the North Atlantic and the associated unique cloud regime can often be identified in visible satellite imagery (e.g., Abel et al., 2017; Brümmer, 1999; Geerts et al., 2022; Renfrew & Moore, 1999; Sanchez et al., 2022; Terpstra et al., 2021). More specifically, Fletcher et al.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of satellite meteorology has evolved our understanding of MCAOs, as its unique cloud regime can often be identified in visible imagery (e.g., Abel et al., 2017; Brümmer, 1999; Geerts et al., 2022; Renfrew & Moore, 1999; Sanchez et al., 2022; Terpstra et al., 2021). Beyond the visible spectrum, clouds and precipitation in remote locations can now be observed via retrievals by CloudSat, a polar‐orbiting satellite with a W‐band radar onboard and measurement capabilities up to |82° ${}^{\circ}$| latitude (Stephens et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in specific aerosol properties caused by the arrival of continental air masses over the ENA region have been described in previous literature. Namely, increased concentrations of submicron aerosol particles have been reported in the Western and Eastern North Atlantic by a number of previous studies (Garrett and Hobbs, 1995;Logan et al, 2014;Pennypacker and Wood, 2017;Sanchez et al, 2022).…”
Section: Introduction 10mentioning
confidence: 92%